Outcome analysis of patients presenting with neurological manifestations of Plasmodium Vivax malaria in tertiary care hospital of Mumbai. - Dilip Salagre, Kaustubh; Nath Sahay, Ravindra; Holkar, Maya (International Journal of Medical Research and Review, 2017)
Objective: Plasmodium vivax (P. vivax) infection has been considered for a long time a benign and self-limited disease. Percentage of complicated cases of vivax malaria is on the increasing trend, cerebral malaria being the most dreaded and a potentially life-threatening complication. Material and Methods: A prospective observational study was done after institutional ethics committee approval from July 2011 to February 2012 at tertiary care hospital in Mumbai. We studied the clinical profile and outcome of all the 48 patients above the age of 12 years diagnosed with Cerebral Malaria. Results: Incidence of neurological manifestations of vivax malaria in our hospital was 14.15%, with 32(66.7%) out of 48 patients being males. The mean age of patients with neurological manifestations of vivax malaria was 29.66 years in discharged patients and 50.88 years in expired patients. Altered sensorium 37(77.1%) followed by convulsion 28(58.3%) were common findings, but focal neurological deficit, Bell’s palsy, ataxia, psychosis were also seen. Mortality was higher (62.5%) in patients with premorbid conditions (p value <0.05) and that of with other system involvements (87.5%) including hepatic, renal, hepatorenal, pulmonary involvement (p value<0.05). Association between outcome with older age & high parasite index patients is significant (p value<0.001), however no such significant association was found in terms of gender distribution. Conclusion: Plasmodium vivax, as has been traditionally believed, is no longer a benign species and is causing presentations akin to P. falciparum. It is imperative that clinicians are aware of and ready to handle the complications caused by Plasmodium vivax.